2005
DOI: 10.3310/hta9380
|View full text |Cite
|
Sign up to set email alerts
|

The causes and effects of socio-demographic exclusions from clinical trials

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
136
1
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 83 publications
2
136
1
11
Order By: Relevance
“…147,148 To ensure the generalisability of the results of this study to the UK population, it is important to have a study population that represents that of the communities in which the rehabilitation would be provided. 153,154 Given concerns about the lower uptake of CR in people from ethnic minority groups, we wanted to explore whether the provision of a home-based programme might improve uptake and adherence in this group. There have been concerns about the underrepresentation of people from ethnic minority groups in clinical trials 153,155 and trials of cardiac patients in particular, 156 but few trials of CR have even reported the ethnicity of their participants.…”
Section: Ethnic Minority Issues Ethnic Minority Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…147,148 To ensure the generalisability of the results of this study to the UK population, it is important to have a study population that represents that of the communities in which the rehabilitation would be provided. 153,154 Given concerns about the lower uptake of CR in people from ethnic minority groups, we wanted to explore whether the provision of a home-based programme might improve uptake and adherence in this group. There have been concerns about the underrepresentation of people from ethnic minority groups in clinical trials 153,155 and trials of cardiac patients in particular, 156 but few trials of CR have even reported the ethnicity of their participants.…”
Section: Ethnic Minority Issues Ethnic Minority Participationmentioning
confidence: 99%
“…153,154 Given concerns about the lower uptake of CR in people from ethnic minority groups, we wanted to explore whether the provision of a home-based programme might improve uptake and adherence in this group. There have been concerns about the underrepresentation of people from ethnic minority groups in clinical trials 153,155 and trials of cardiac patients in particular, 156 but few trials of CR have even reported the ethnicity of their participants. Exclusion of ethnic minorities from clinical trials undermines the UK Government's NHS plan for tackling inequalities and its core principle of providing culturally appropriate and accessible care for different groups and individuals.…”
Section: Ethnic Minority Issues Ethnic Minority Participationmentioning
confidence: 99%
“…En este tema se encuentran enfrentadas distintas opiniones, no existiendo una valoración unánime ni en cuanto en la necesidad de evitarlo ni en sus consecuencias [2][3][4][5][6][7] .…”
Section: Introductionunclassified
“…Bartlett et al, 2005, andBornhöft et al, 2006) clearly highlighting the tension between features that safeguard internal validity (such as the randomisation itself, placebo and blinding) but at the same time worsen external validity or indeed generate or exacerbate what we call randomisation bias.…”
Section: Introductionmentioning
confidence: 99%
“…To this regard, a number of authors (e.g. Britton et al, 1998, Bartlett et al, 2005, and Van Spall et al, 2007 have advocated as the immediate priority the improvement of the quality of reporting, as information on eligibility criteria and participation is often simply lacking even for RCTs published in major medical journals.…”
mentioning
confidence: 99%